The Corporate governance, agency cost and firm performance: evidence from China - Zhang, Luchun (2018)
Based on agency theory, the agency cost in the process of corporate governance can be divided in to type I agency cost between management and shareholders and type II agency cost between majority shareholders and minority shareholders. This paper brought corporate governance mechanisms, two types of agency cost and firm performance into a uniform analytic framework. Then, I built a mediation effect model of corporate governance, agency cost, firm performance based on the mediation effect testing procedures presented by Zhao et al. (2010). It conducted the empirical research based on the panel data from 1295 public listed companies in Shanghai stock exchange during 2014 to 2017 and adapted the fixed effect model. The research tested the impact of corporate governance mechanisms on firm performance, agency cost and the mediation effect of two kinds of agency cost on the relationship of corporate governance and firm performance. Results of the study indicated that: Type I agency cost has partly mediating effect in ownership concentration, independent of board management incentive and firm performance. These corporate governance mechanisms can effectively promote firm performance by reducing type I agency cost. Type II agency cost also have a mediating effect in ownership concentration, independence of board and management incentive. However, the mediating effect of type II agency in the relationship between ownership concentration and management incentive is that excessive concentration and equity incentive will decrease the firm performance by increasing type II agency cost.